Theoretical aspects of optimizing information and communication costs in construction activities based on digital technologies - Ivakhnenko, I.; Sarhsian, V.; Movchan, M.; Hura, Ye.; Sharshun, F. (Ways to Improve Construction Efficiency, 2024)
In the current conditions of digital transformation of the economy, construction enterprises face the necessity of optimizing information and communication costs, which directly affect their efficiency, competitiveness, and resilience. The study emphasizes the theoretical aspects of managing such costs, which are considered as a strategic resource for the development of construction activities. Expenditures on information and communication technologies form the foundation of a company’s digital infrastructure, ensuring effective management, quality control, process monitoring, and operational transparency. Optimization of information and communication costs is related not only to economic approaches but also to the integration of modern digital technologies, such as cloud platforms, project management systems, ERP solutions, artificial intelligence, and Big Data analytics. The paper highlights that expenditures on information and communication resources should be viewed not as passive, but as active investments capable of generating long-term added value. Particular attention is paid to analyzing the efficiency of distributing these costs in the context of building digital ecosystems in the construction industry. The study evaluates opportunities to reduce unproductive expenditures, increase labor productivity, and minimize risks arising in the use of information systems. Approaches to cost modeling are considered, taking into account both direct and indirect benefits of digitalization, including the reduction of administrative expenses, acceleration of managerial decision-making, and improvement of forecasting accuracy. The research substantiates that strategic management of information and communication costs is an essential factor for the sustainability of construction companies in a highly competitive environment. Digital tools allow the creation of integrated control systems, where expenditures correlate with performance outcomes. In the long-term perspective, optimization of these costs contributes not only to resource savings but also to the formation of competitive advantages in the market. Thus, the development of theoretical aspects of optimizing information and communication costs in construction activities based on digital technologies represents a relevant scientific task with significant practical potential.